Exploring provision of Innovative Community Education Placements (ICEPs) for junior doctors in training: a qualitative study. Issue 2 (9th February 2016) - Griffin, Ann; Jones, Melvyn M; Khan, Nada; Park, Sophie; Rosenthal, Joe; Chrysikou, Vasiliki
Abstract : Objective: Medical education in community settings is an essential ingredient of doctors' training and a key factor in recruiting general practitioners (GP). Health Education England's report 'Broadening the Foundation' recommends foundation doctors complete 4-month community placements. While Foundation GP schemes exist; other community settings, are not yet used for postgraduate training. The objective of this study was to explore how community-based training of junior doctors might be expanded into possible 'innovative community education placements' (ICEPs), examining opportunities and barriers to these developments. Design: A qualitative study where semistructured interviews were undertaken and themes were generated deductively from the research questions, and iteratively from transcripts. Setting: UK community healthcare. Participants: Stakeholders from UK Community healthcare providers and undergraduate GP and community educators. Results: Nine participants were interviewed; those experienced in delivering community-based undergraduate education, and others working in community settings that had not previously trained doctors. Themes identified were practicalities such as 'finance and governance', 'communication and interaction', 'delivery of training' and 'perceptions of community'. ICEPs were willing to train Foundation doctors. However, concerns were raised that large numbers and inadequate resources could undermine the quality of educational opportunities, and even cause reputational damage. Organisation was seen as a challenge, which might be best met by placing some responsibility with trainees to manage their placements. ICEP providers agreed that defined service contribution by trainees was required to make placements sustainable, and enhance learning. ICEPs stated the need for positive articulation of the learning value of placements to learners and stakeholders. Conclusions: This study highlighted the opportunities for foundation doctors to gain specialist and generalist knowledge in ICEPs from diverse clinical teams and patients. We recommend in conclusion ways of dealing with some of the perceived barriers to training.